Preventive Effect of Hochu-ekki-to on Lipopolysaccharide-Induced Acute Lung Injury in BALB/c Mice - Tajima, Shunji (Lung, 2006)
This study was designed to investigate the effect of Hochu-ekki-to (TJ-41), a Japanese herbal medicine, on the development of lipopolysaccharide (LPS)-induced acute lung injury (ALI) in mice. ALI was induced in female BALB/c mice by the intranasal administration of 0.1 mg/kg LPS. The mice were divided into a group receiving normal feed and another group receiving feed mixed with TJ-41 at a dose of 1 g/kg/day for 8 weeks before LPS challenge. In the bronchoalveolar lavage fluid, the preadministration of TJ-41 caused significant reduction in the absolute number of total cells, neutrophils, and macrophages. The preadministration of TJ-41 significantly inhibited increases in the serum level of keratinocyte chemoattractant (KC), which is a murine chemotaxin for neutrophils that corresponds to human interleukin-8, with respect to its concentration at 24 h after LPS challenge. Furthermore, the histopathologic findings indicated that alveolitis with leukocyte infiltration in the alveolar space was less severe in the TJ-41-treated mice than in the control mice. These findings indicated that the preadministration of TJ-41 could show an inhibitory effect on ALI in this experimental murine system associated with the suppression of chemokine production.